Advanced Porous Materials in Mixed Matrix Membranes - Cheng, Youdong; Ying, Yunpan; Japip, Susilo; Jiang, Shu‐Dong; Chung, Tai‐Shung; Zhang, Sui; Zhao, Dan (Advanced materials (Weinheim), 2018)
Membrane technology has gained great interest in industrial separation processing over the past few decades owing to its high energy efficiency, small capital investment, environmentally benign characteristics, and the continuous operation process. Among various types of membranes, mixed matrix membranes (MMMs) combining the merits of the polymer matrix and inorganic/organic fillers have been extensively investigated. With the rapid development of chemistry and materials science, recent studies have shifted toward the design and application of advanced porous materials as promising fillers to boost the separation performance of MMMs. Here, first a comprehensive overview is provided on the choices of advanced porous materials recently adopted in MMMs, including metal–organic frameworks, porous organic frameworks, and porous molecular compounds. Novel trends in MMMs induced by these advanced porous fillers are discussed in detail, followed by a summary of applying these MMMs for gas and liquid separations. Finally, a concise conclusion and current challenges toward the industrial implementation of MMMs are outlined, hoping to provide guidance for the design of high‐performance membranes to meet the urgent needs of clean energy and environmental sustainability. The recent research progress in exploring various types of advanced porous materials as promising fillers in mixed matrix membranes (MMMs) is summarized. Along with this, novel MMM design and enhanced membrane separation performance induced by these advanced porous fillers are discussed in detail. Finally, current challenges and future directions for industrial implementation of these MMMs are highlighted.